Composite nanometer zero-valent iron filler and preparation method thereof

By combining nano zero-valent iron with dispersants, gel-like substances and lightweight porous sponges, composite nano zero-valent iron fillers are prepared, which solves the problems of easy agglomeration, oxidation and biotoxicity of nano zero-valent iron in anaerobic digestion technology, and achieves more efficient methane gas production and stability.

CN115872524BActive Publication Date: 2025-03-11NANJING UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211569605.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-08
Publication Date
2025-03-11
Estimated Expiration
2042-12-08

AI Technical Summary

Technical Problem

In the existing anaerobic digestion technology, nano zero-valent iron particles are prone to agglomeration, oxidation, and surface passivation, resulting in biotoxicity and sludge mineralization problems, affecting the long-term operation of the anaerobic reactor.

Method used

The preparation method of composite nano zero-valent iron filler is adopted to combine nano zero-valent iron with dispersant, gel-like substances and lightweight porous sponge to form nano zero-valent iron turbid liquid gel-like substances, and cross-link them through hardening and cross-linking of calcium chloride saturated boric acid solution to prepare a stable nano zero-valent iron composite filler.

Benefits of technology

This method allows nano zero-valent iron to be released slowly during the reaction process, reduces biotoxicity, improves stability and fluidity, significantly reduces the iron ion content in water, alleviates the problem of sludge mineralization, and improves methane gas production efficiency in the anaerobic reactor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115872524B_ABST
    Figure CN115872524B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite nano zero-valent iron filler and a preparation method thereof, and belongs to the field of water treatment. The composite nano zero-valent iron filler of the present invention comprises nano zero-valent iron, a dispersant solution, a gel-like substance, and a lightweight porous sponge; the dispersant solution comprises: water, starch, dextrin, acetylacetone and ascorbic acid; the gel-like substance comprises: polyvinyl alcohol, sodium alginate, carboxymethyl cellulose, EDTA, EPS-microbial agent. The preparation method of the composite nano zero-valent iron of the present invention comprises four steps of preparing nano zero-valent iron turbid solution, preparing gel-like substance, adding porous sponge and cross-linking hardening. The main purpose of the present invention is to maintain the high reactivity of nano zero-valent iron, prolong the reaction life of nano zero-valent iron, and improve the dispersion fluidity and mechanical strength of nano zero-valent iron in the aqueous phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water treatment, and more specifically to a composite nanometer zero-valent iron filler and a preparation method thereof. Background Art

[0002] At present, anaerobic digestion technology is widely used to treat degradable organic pollutants, and the methane produced by treating pollutants is used as biogas for renewable energy. However, existing anaerobic digestion technologies generally have problems such as low biogas conversion rate and poor stability, resulting in the lack of obvious energy recovery and economic benefits of anaerobic digestion facilities. Studies have found that adding nanoscale zero valent iron (NZVI) to anaerobic biochemical systems is a good way to enhance anaerobic methanogenesis, but long-term addition of nanoscale zero valent iron will lead to a decrease in the content of polysaccharides and proteins in the soluble microbial products (SMP) of anaerobic granular sludge, and the activity of methanogens will be affected to a certain extent.

[0003] Nano-zero-valent iron (NZVI) refers to zero-valent iron particles with a particle size between 1 and 100 nm. It has a large specific surface area and surface energy, which makes it have excellent adsorption and high reducibility, and produces unique surface effects and small size effects to improve reactivity. It is precisely because of the unique advantages of nano-zero-valent iron that it is "easy to agglomerate", "easy to oxidize", and it is easy to produce hydroxides and metal carbonates when degrading pollutants in water, which adhere to the surface of NZVI and passivate it, making it difficult for NZVI to maintain its activity for a long time.

[0004] In addition, due to the "core-shell structure" of NZVI, the outer shell is mainly composed of iron oxide or hydroxyl iron, which makes the nano-iron particles have chemical bonding and adsorption functions, and easily combine with phosphates in wastewater to form precipitates, which are deposited in the granular sludge bed at the bottom of the reactor, not only causing the loss and waste of NZVI, but also causing the accumulation of iron sludge in the anaerobic system, producing chemical sludge and biological toxicity, inhibiting the microbial activity of granular sludge, and being unfavorable for the long-term operation of anaerobic reactors and other engineering application problems.

[0005] According to the search, the invention patent named Porous Nano Zero-Valent Iron and Porous Nano Zero-Valent Iron Composite Materials (Publication No.: CN105081305B) discloses a porous nano zero-valent iron composite material composed of a main active component, a skeleton component and an auxiliary component, wherein the main active component is nano zero-valent iron, the skeleton component is composed of one or more metals selected from Al, Mn, Si, and Zn, and the auxiliary component is selected from one or more of Ni, Pt, La, Cu, and Pd.

[0006] The invention patent is entitled "A method for preparing zero-valent nano iron particles (publication number: CN104308173B)", which discloses the following steps: 1) mixing an aqueous solution of a soluble iron salt with a polyelectrolyte to obtain a polymer solution, and performing electrospinning to obtain a nanofiber felt; 2) under anaerobic conditions, reacting an aqueous solution of a reducing agent with the nanofiber felt obtained in step 1), and collecting the resulting precipitate after the reaction is completed, which is the zero-valent nano iron particle.

[0007] Through the analysis of existing technologies, it was found that the existing composite nano zero-valent iron fillers lack the design for application in anaerobic treatment equipment. During the operation of anaerobic treatment equipment, nano zero-valent iron particles are prone to agglomeration, oxidation, surface passivation, and biological toxicity and sludge mineralization caused by long-term addition of NZVI. Summary of the invention

[0008] 1. Technical problem to be solved by the invention

[0009] In view of the problems of agglomeration, oxidation, surface passivation, biological toxicity and sludge mineralization caused by long-term addition of nano zero-valent iron in the application of the prior art, the present invention provides a composite nano zero-valent iron filler and a preparation method thereof.

[0010] 2. Technical solution

[0011] To achieve the above object, the first aspect of the present invention relates to a method for preparing a composite nano zero-valent iron filler, which specifically comprises the following steps:

[0012] S10: preparing nano zero-valent iron turbid solution: adding nano zero-valent iron into the dispersant solution and stirring evenly to form nano zero-valent iron turbid solution;

[0013] S20: preparing a gel-like substance: adding polyvinyl alcohol, sodium alginate, carboxymethyl cellulose, EDTA, and EPS-microbial agent into water and stirring until a uniform paste is formed to form a gel-like substance;

[0014] S30: adding a light porous sponge: weighing the nano zero-valent iron turbid liquid and the gel-like substance according to a weight ratio, stirring them evenly to form a nano zero-valent iron turbid liquid gel-like substance, and adding a light porous sponge so that the nano zero-valent iron turbid liquid gel-like substance is adsorbed on the light porous sponge;

[0015] S40: cross-linking and hardening: adding the lightweight porous sponge adsorbing the nano zero-valent iron turbid liquid gel-like substance into a saturated boric acid solution containing 2% to 3% calcium chloride to harden and cross-link for 10 to 20 hours to prepare a nano zero-valent iron composite filler;

[0016] In the steps S10 to S40, nitrogen is continuously introduced for protection.

[0017] Furthermore, the weight components of the nano zero-valent iron turbid solution in step S10 are: 40-50 parts of nano zero-valent iron and 50-60 parts of dispersant solution.

[0018] Furthermore, the dispersant solution described in step S10 includes: water, starch, dextrin, acetylacetone and ascorbic acid, and the weight components of the dispersant solution are: 85-95 parts of water, 3-8 parts of starch, 0.5-1 part of dextrin, 1-5 parts of acetylacetone, and 0.5-1 part of ascorbic acid.

[0019] Furthermore, the gel-like substance in step S20 is composed of 10 to 20 parts by weight of polyvinyl alcohol, 5 to 10 parts of sodium alginate, 4 to 8 parts of carboxymethyl cellulose, 6 to 12 parts of EDTA and 50 to 75 parts of EPS-microbial agent.

[0020] Furthermore, the EPS-microbial agent is composed of extracellular polymers and microbial liquid in a weight ratio of 1:50, and the colony count of the microbial liquid is 1×10 9 ~1×10 10 cfu / mL.

[0021] Furthermore, the microorganisms in the microbial liquid include one or more of hydrolytic bacteria, fermentative bacteria, acetic acid bacteria, and methanogens, and the microbial liquid includes trace elements such as Zn, Mn, Co, Ni, Mo, and Se.

[0022] Furthermore, the water temperature in step S20 is 50 to 60 degrees Celsius, and the water temperature duration is 10 to 30 minutes.

[0023] Furthermore, the weight ratio of the nano-iron turbid liquid to the gel-like substance in step S30 is 1:3; the lightweight porous sponge in step S30 is a cube or spherical particle, the cube side length and sphere diameter are 8-10 mm, the particle pore size is 20-30 PPI, and the density is 0.5-0.7 g / cm 3 .

[0024] The second aspect of the present invention relates to a composite nano zero-valent iron filler, which is prepared by a preparation method of a composite nano zero-valent iron filler according to the first aspect of the present invention, and includes nano zero-valent iron, a dispersant solution, a gel-like substance, and a lightweight porous sponge; the dispersant solution includes water, starch, dextrin, acetylacetone, and ascorbic acid; the gel-like substance includes polyvinyl alcohol, sodium alginate, carboxymethyl cellulose, EDTA, and EPS-microbial agent.

[0025] Furthermore, the weight components of the dispersant solution are: 85-95 parts of water, 3-8 parts of starch, 0.5-1 part of dextrin, 1-5 parts of acetylacetone, and 0.5-1 part of ascorbic acid; the weight components of the gel-like substance are: 10-20 parts of polyvinyl alcohol, 5-10 parts of sodium alginate, 4-8 parts of carboxymethyl cellulose, 6-12 parts of EDTA, and 50-75 parts of EPS-microbial agent;

[0026] Furthermore, the density of the composite nano zero-valent iron filler is 0.98-1.15 g / cm 3 , the shape is a sphere and / or a cube, the side length of the cube and the diameter of the sphere are 8 to 10 mm.

[0027] The third aspect of the present invention relates to a method for using a composite nano zero-valent iron filler, comprising the following steps:

[0028] The first step: adding the composite nano zero-valent iron filler into the anaerobic reaction device and running it for 30 to 90 days;

[0029] Step 2: crushing: when the nano zero-valent iron filler put into the anaerobic reaction device turns purple or brown, 10% to 50% of the nano zero-valent iron filler is separated and crushed;

[0030] Step 3: Cultivation, transferring the nano zero-valent iron filler crushed in the second step to the cultivation area of ​​the anaerobic reaction device for cultivation, and maintaining the normal operation of the anaerobic reaction device;

[0031] Step 4: Storage: The nanometer zero-valent iron filler in the culture area of ​​the anaerobic reaction device is discharged through the mud discharge pipe of the anaerobic reactor, and the discharged nanometer zero-valent iron filler is collected and stored.

[0032] 3. Beneficial effects

[0033] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:

[0034] (1) The preparation method of composite nano zero-valent iron of the present invention comprises four steps S10 to S40. During the preparation process, starch and dextrin are used as nano zero-valent iron dispersants, and acetylacetone and ascorbic acid are used as indicators and protective agents of nano zero-valent iron. During the preparation process, the nano zero-valent iron is uniformly dispersed. By combining with a gel-like substance and a lightweight porous sponge, the nano zero-valent iron is slowly released during the reaction process, thereby reducing the biological toxicity of the nano zero-valent iron and improving the stability and fluidity of the nano zero-valent iron filler.

[0035] (2) The nano zero-valent iron filler of the present invention can adsorb iron ions produced by nano iron during anaerobic corrosion in water, significantly reducing the iron ion content in water. At the same time, the nano zero-valent iron filler of the present invention can adsorb phosphate in water, which can alleviate the sludge mineralization and biological toxicity problems caused by long-term addition of nano zero-valent iron. In addition, the composite nano zero-valent iron filler of the present invention contains a conductive medium, which is beneficial to the interspecies electron transfer of methanogenic microorganisms and improves the methane production efficiency in the reactor. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a flow chart of the preparation method of the composite nano zero-valent iron filler of the present invention;

[0037] Figure 2 A structural diagram of the composite nanofiller of the present invention;

[0038] Figure 3 Another structural diagram of the composite nanofiller of the present invention;

[0039] Figure 4 It is an anaerobic reaction device;

[0040] Figure 5 It is a structural schematic diagram of the grid A of the anaerobic reaction device;

[0041] Figure 6 The treatment effect diagram of the anaerobic device from the 1st to the 12th month.

[0042] Description of Figure Numbers:

[0043] 1. Gas delivery valve; 2. Three-phase separator gas delivery pipe; 3. Sewage return pipe; 31. Sewage return valve; 4. Filler delivery pipe; 41. Delivery valve; 5. Water circulation pipe; 51. Circulation pump; 6. Mud discharge pipe; 61. Mud discharge valve; 7. Gas delivery connecting pipe; 8. Water outlet weir; 81. Water outlet channel;

[0044] 10. Hydrolysis reactor; 11. Three-phase separator A; 12. Grid D; 13. Water inlet distribution pipe; 14. Grid A; 141. Perforated plate; 142. Hinge; 143. Pull rope A; 144. Inner wall roller; 145. Top roller; 15. Grid E; 16. Flow pusher;

[0045] 20. Methane reactor; 21. Three-phase separator B; 22. Grid B; 23. Grid C; 24. Water distribution pipe; 241. Water outlet hole; 242. Water outlet pipe; 25. Guide rail;

[0046] 30. Feeding device; 301. Feeding port; 302. Feeding pipe; 303. Float; 304. Pull rope; 305. Roller; 306. Bracket. DETAILED DESCRIPTION

[0047] To further understand the content of the present invention, Figure 1 , Attachment Figure 2 The present invention is described in detail with reference to the accompanying drawings and examples.

[0048] The structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions for the implementation of the present invention, so they have no substantial technical significance. Any modification of the structure, change of the proportion relationship or adjustment of the size, without affecting the effects and purposes that can be achieved by the present invention, should still fall within the scope of the technical content disclosed by the present invention. At the same time, the terms such as "upper", "lower", "left", "right", "middle" and so on quoted in this specification are only for the convenience of description, and are not used to limit the scope of implementation. The change or adjustment of their relative relationship should also be regarded as the scope of implementation of the present invention without substantially changing the technical content.

[0049] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or manufacturer recommendations. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased from the market.

[0050] Example 1

[0051] Combination Figures 1 to 3 This embodiment relates to a method for preparing a composite nano zero-valent iron filler, and the filler preparation method includes steps S10-S40:

[0052] S10 Preparation of nano zero-valent iron turbid solution: Add a certain weight of nano zero-valent iron into a dispersant solution, and stir to obtain a uniformly dispersed nano zero-valent iron turbid solution. The dispersant solution includes water, starch, dextrin, acetylacetone and ascorbic acid. Nano zero-valent iron, starch, dextrin, acetylacetone and ascorbic acid are conventional products that can be purchased from the market.

[0053] If the weight component of one part of nano zero-valent iron turbid solution is 100 parts, then the weight component of nano zero-valent iron is 40-50 parts, and the weight component of dispersant solution is 50-60 parts, that is, when the weight component of nano zero-valent iron is 40, the weight component of dispersant solution is 60 parts; when the weight component of nano zero-valent iron is 50 parts, the weight component of powder solution is 50 parts; when the weight component of nano zero-valent iron is 45 parts, the weight component of powder solution is 55 parts.

[0054] If the weight component of one dispersant solution is 100 parts, the weight components of the dispersant are as follows: 85-95 parts of water, 3-8 parts of starch, 0.5-1 parts of dextrin, 1-5 parts of acetylacetone, and 0.5-1 parts of ascorbic acid. Alternatively, 85 parts of water, 8 parts of starch, 1 part of dextrin, 5 parts of acetylacetone, and 1 part of ascorbic acid. Alternatively, 95 parts of water, 3 parts of starch, 0.5 parts of dextrin, 1 part of acetylacetone, and 0.5 parts of ascorbic acid.

[0055] S20 Preparation of gel-like substance: Add polyvinyl alcohol, sodium alginate, carboxymethyl cellulose, disodium ethylenediaminetetraacetate (EDTA), and EPS-microorganism agent to water and stir until a uniform paste is formed to form a gel-like substance. Polyvinyl alcohol, sodium alginate, carboxymethyl cellulose, and EDTA can all be purchased from the market, and the weight proportion of the gel-like substance formed is 10-20 parts of polyvinyl alcohol, 5-10 parts of sodium alginate, 4-8 parts of carboxymethyl cellulose, 6-12 parts of EDTA, and 50-75 parts of EPS-microorganism agent, or 10 parts of polyvinyl alcohol, 5 parts of sodium alginate, 4 parts of carboxymethyl cellulose, 6 parts of EDTA, and 75 parts of EPS-microorganism agent, or 20 parts of polyvinyl alcohol, 10 parts of sodium alginate, 8 parts of carboxymethyl cellulose, 12 parts of EDTA, and 50 parts of EPS-microorganism agent, or 15 parts of polyvinyl alcohol, 7 parts of sodium alginate, 6 parts of carboxymethyl cellulose, 9 parts of EDTA, and 63 parts of EPS-microorganism agent.

[0056] The EPS-microbial agent is composed of EPS (extracellular polymer) and microbial liquid in a weight ratio of 1:50, and the colony count of the microbial liquid is 1×10 9 ~1×10 10 cfu / mL, the bacterial solution is rich in nutrients required by microorganisms and trace elements such as Zn, Mn, Co, Ni, Mo, and Se, and the water temperature is preferably 50-60°C for 10-30 minutes. The types of microorganisms in the bacterial solution are preferably one or more of hydrolytic bacteria, fermentative bacteria, acetic acid bacteria, and methanogens.

[0057] S30: Add the nano zero-valent iron turbid liquid prepared in step S10 to the gel-like substance prepared in step S20, the weight ratio of the nano zero-valent iron turbid liquid to the gel-like substance is 1: (1-3), and after being fully stirred, a gel-like substance containing the nano zero-valent iron turbid liquid is formed, and its weight composition ratio is 1 part of S10 nano zero-valent iron turbid liquid and 1-3 parts of S20 gel-like substance, or 1 part of S10 nano zero-valent iron turbid liquid and 1 part of S20 gel-like substance, or 1 part of S10 nano zero-valent iron turbid liquid and 2 parts of S20 gel-like substance, or 1 part of S10 nano zero-valent iron turbid liquid and 3 parts of S20 gel-like substance. After the above operation is completed, a light porous sponge material is added, and the gel-like substance containing the nano zero-valent iron turbid liquid is adsorbed in the light porous sponge by squeezing and then releasing or stirring. The porous sponge material has an appearance of sphere, cuboid, cube, prism, etc., preferably cube and sphere, and cube and sphere particles can also be added at the same time. The pore size of the porous sponge material is preferably 20-30 PPI, the side length of the cube particles and the diameter of the sphere are preferably 8-10 mm, and the density is 0.5-0.7 g / cm 3 .

[0058] S40: The adsorbed sponge material is added to a saturated boric acid solution containing 2% to 3% calcium chloride to harden and crosslink for 10 to 20 hours to prepare a nano zero-valent iron composite filler.

[0059] In the above steps S10 to S40, nitrogen is continuously introduced for protection during the preparation of the dispersant solution, the nano-zero-valent iron turbid solution, and the gel material, and the water solvent used in the preparation of the dispersant solution and the nano-zero-valent iron turbid solution must be stripped with nitrogen to remove the dissolved oxygen in the water.

[0060] Example 2

[0061] This embodiment relates to a composite nanometer zero-valent iron filler, which is manufactured by the preparation method of the composite nanometer zero-valent iron filler described in Example 1. The components of the composite nanometer zero-valent iron filler are shown in Table 1:

[0062] Table 1 Composite nano zero-valent iron filler composition

[0063]

[0064] Referring to Table 1, the composite nano zero-valent iron filler of this embodiment includes nano zero-valent iron, a dispersant solution, a gel-like substance, and also includes a lightweight porous sponge, nano zero-valent iron, a dispersant solution, a gel-like substance, and a lightweight porous sponge.

[0065] The dispersant solution includes water, starch, dextrin, acetylacetone and ascorbic acid. The weight proportion of the dispersant is preferably: 85-95 parts of water, 3-8 parts of starch, 0.5-1 part of dextrin, 1-5 parts of acetylacetone, and 0.5-1 part of ascorbic acid.

[0066] The gel-like substance includes polyvinyl alcohol, sodium alginate, carboxymethyl cellulose, and EDTA. The weight ratio of the gel-like substance is preferably 10 to 20 parts of polyvinyl alcohol, 5 to 10 parts of sodium alginate, 4 to 8 parts of carboxymethyl cellulose, 6 to 12 parts of EDTA, and 50 to 75 parts of EPS-microbial agent. Among them, EPS-microbial agent is composed of EPS (extracellular polymer) and microbial liquid in a weight ratio of 1:50, and the number of colonies of microbial liquid is 1×10 9 ~1×10 10 cfu / mL, the bacterial solution is rich in nutrients required by microorganisms and trace elements such as Zn, Mn, Co, Ni, Mo, and Se, and the water temperature is preferably 50-60°C for 10-30 minutes. The types of microorganisms in the bacterial solution are preferably one or more of hydrolytic bacteria, fermentative bacteria, acetic acid bacteria, and methanogens.

[0067] The porous sponge material has an appearance of sphere, cuboid, cube, prism, etc., preferably cube and sphere, and cube and sphere particles can also be added at the same time. The pore size of the porous sponge material is preferably 20-30 PPI, the side length of the cube particles and the diameter of the sphere are preferably 8-10 mm, and the density is 0.5-0.7 g / cm 3 .

[0068] As shown in Table 1, the proportion of the same-grade materials of the composite nano zero-valent iron filler in this embodiment can be freely combined within the range specified in Table 1. For example, the secondary materials of the nano iron turbid liquid in S10 are nano iron and dispersant, wherein the nano iron component accounts for 40-50, and the dispersant component accounts for 50-60. There may be infinite combinations of nano iron turbid liquids. When the nano iron component accounts for 40, the dispersant component accounts for 60. When the nano iron component accounts for 50, the dispersant component accounts for 50. The nano iron component is 45 and the dispersant component accounts for 55. There are infinite combinations, which are not listed one by one in this embodiment.

[0069] The composite nano-zero-valent iron of this embodiment uses the nano-zero-valent iron in the nano-iron turbid solution in step S10 in Example 1 as the main body of the composite material, wherein starch and dextrin are used as nano-iron dispersants to evenly disperse the nano-iron. Since nano-zero-valent iron has strong reducibility and poor stability, it is not conducive to storage. Ascorbic acid and dispersants are used as nano-iron protective agents to prevent it from being oxidized during the preparation process. Acetylacetone is used as a composite material loss indicator. With the long-term use of the nano-zero-valent iron composite material, the color of the material gradually deepens, and the material is evaluated to enter the next system for reuse. In addition, the presence of a conductive medium in the composite nano-zero-valent iron filler is beneficial to the interspecies electron transfer of methanogenic microorganisms and improves the methane gas production efficiency in the reactor.

[0070] To further illustrate the effect of the composite nano zero-valent iron filler of this embodiment, the experimental fillers were prepared by the composite nano zero-valent iron filler preparation method of Example 1. The filler codes are A1-A3, B1-B3, C1-C3, and the density of the filler is 0.98-1.15 g / cm 3 The shape is a sphere and / or a cube, etc. The side length of the cube and / or the diameter of the sphere is 8 to 10 mm. The main material parameters and product properties during the preparation process are shown in Table 2.

[0071] Table 2 Main material parameters of experimental fillers

[0072]

[0073]

[0074] 13 groups of anaerobic experimental devices were used to treat bio-fermentation pharmaceutical wastewater. The device numbers were 0# to 13#. The volume of each group of anaerobic reactors was 1m 3 , HRT = 48h, processing capacity is 0.5m 3 / d, 275kg of mature anaerobic granular sludge was inoculated in the reactor, the inlet COD concentration was 10500mg / L, the pH value was 6.5-7.5, and the temperature was 30-35℃. After two months of stable operation under the same conditions, the effluent COD (Chemical Oxygen Demand, hereinafter referred to as COD) of the 13 groups of anaerobic devices was not much different, and the removal rate was about 75%, and then the comparative experiment was started. A1, A2, A3, B1, B2, B3, C1, C2, and C3 fillers prepared according to Example 1 were added to the 1#~9# experimental devices respectively as experimental groups; anaerobic granular sludge was added to 0# as a blank group; nano-iron turbid liquid was added as comparison group 1, nano-iron turbid liquid gel-like substance was added as comparison group 2, and porous sponge filler was added as comparison group 3; according to the characteristics of the material itself, the material addition plan was optimized to maximize the advantages of the material itself. The filler addition method of each experimental device is as follows:

[0075] Blank group: no added fillers or reagents.

[0076] The optimization plan for adding materials in the experimental group: adding in four times, once every three months, adding 12kg once in the first month of the comparative experiment, adding 9kg in the beginning of the fourth month, adding 6kg in the beginning of the seventh month, and adding 3kg in the beginning of the tenth month. It is advisable to add nano zero-valent iron filler in batches in appropriate amounts, gradually building a filler-directional microbial enhancement system, which is conducive to improving the anaerobic treatment effect.

[0077] Comparison Group 1 material dosing optimization plan: dosing in six times, once every two months, 1 kg each time, a total of 6 kg. Nano-iron turbidity has a strong reducibility, and a one-time dosing will cause material loss, impact on the system, and sludge mineralization, seriously affecting the normal operation of the system.

[0078] Comparative Group 2 material addition optimization plan: Add in four times, once every three months, 3kg each time, a total of 12kg. Nano iron turbidity gel material, appropriate amount of addition is appropriate, adding too much at a time will affect the anaerobic system granular sludge fluidization effect, so without affecting the normal operation of the anaerobic system, it is appropriate to adopt the above optimization plan.

[0079] Optimization plan for material addition in comparison group 3: At the beginning of the comparison experiment, 200L was added at one time.

[0080] All experimental groups, blank groups, and control groups were operated directly under the same conditions to start the effect comparison experiment. After 12 consecutive months of operation, the average COD value of the anaerobic device effluent, the cumulative methane production after the end of operation, and the sludge VSS / TSS results are shown in Table 3.

[0081] Table 3 Treatment effect of anaerobic device

[0082]

[0083]

[0084] From Table 3, it can be concluded that the average COD concentration of the effluent of the experimental device of the 9 experimental groups is 768 mg / L, and the average removal rate is 93%. Compared with the experimental device of the blank group, the COD removal rate of the experimental group increased by 16%, and the methane production increased by 27%. Similarly, compared with the comparison groups 1 to 3, the COD removal effect and methane production of the experimental device of the experimental group are significantly better than those of the comparison group. The sludge VS / TS data results show that the VSS / TSS (VSS / TSS represents the proportion of anaerobic bacteria in granular sludge. The higher the ratio, the higher the proportion of anaerobic bacteria. The high ratio can generally reach 0.8; the low ratio is due to the fact that there are more inert substances in it, and the corresponding activity is also worse. The low ratio can reach 0.3) values ​​of the experimental group anaerobic granular sludge are higher than those of the blank group and the comparison groups 1 to 3, among which the comparison group 1 has the lowest value. The experiment shows that the long-term addition of nano-iron turbidity will cause sludge mineralization, inhibit microbial activity, and reduce methane production.

[0085] The average monthly effluent COD values ​​of the nine experimental groups and the control group 1 were compared and analyzed. The results are shown in Table 4.

[0086] Table 4 Average COD concentration of effluent from anaerobic device from 1st to 12th month

[0087]

[0088]

[0089] As can be seen from Table 4, the effluent COD of the experimental device from 1 to 12 months of operation are as follows: experimental group, comparison group 2, comparison group 3, comparison group 1 and blank group from low to high, and the experimental group has the best treatment effect.

[0090] Combination Figure 6 , the COD of the effluent of the control group 1 was lower than that of the blank group in the first to ninth months, and the COD of the effluent of the experimental group was not much different in the first 1 to 2 months. As the operation time prolonged, the treatment effect gradually widened with the experimental group, and even in October, the effluent COD was higher than that of the blank group. Moreover, after each addition of nano-iron turbidity, the effluent COD would be lower than that of the previous month, but the treatment effect could only be maintained for about 1 month. With the continuous addition of nano-iron turbidity, the effluent COD of the anaerobic device showed an overall upward trend. Compared with control groups 2 and 3, the overall treatment effect of control group 1 was lower than that of control group 2, better than control group 3 from January to May, and lower than control group 3 from June to December.

[0091] The experiment of comparison group 1 shows that nano-iron turbidity is beneficial to improving the treatment effect of the anaerobic system, but continuous addition will also bring about the problem of sludge poisoning and mineralization, resulting in increasingly poor treatment effects.

[0092] Combination Figure 6In the initial stage of operation, the treatment effect of the comparison group 2 was not much different from that of the experimental group. The initial addition of nano-iron gel-like substances contributed to the rapid anaerobic reaction. However, with long-term operation, the problems of the added nano-iron gel-like substances gradually emerged. This was mainly due to the large density of the nano-iron gel-like substances and poor fluidity in the reactor. It failed to flow fully in the reaction zone and concentrated in the lower area of ​​the reactor. Long-term operation would cause sludge solidification and mineralization problems.

[0093] Combination Figure 6 ,Table 3, compared with the blank group, the COD removal rate of comparison group 3 increased by 7.3%, and the methane production increased by 11.1%, indicating that the porous sponge filler has formed a biofilm, which helps to increase the microbial content in the anaerobic device, thereby improving the treatment effect of the anaerobic device.

[0094] In summary, the addition of nano-iron turbid liquid and nano-iron gel-like substance can play a certain beneficial role in a short period of time, but it is not suitable for long-term addition. Although the addition of porous sponge particles can also play a role in improving the effect, the effect is relatively slow and the improvement effect is limited. The experimental results of the nano zero-valent iron filler of the present invention show that the above problems are effectively solved.

[0095] Example 3

[0096] This embodiment provides a method for using a composite nanometer zero-valent iron filler, wherein the composite nanometer zero-valent iron filler is manufactured by the method described in Example 1. Specifically, the method comprises the following steps:

[0097] The first step is to add the composite nano zero-valent iron filler into the anaerobic reaction device. The volume of the composite nano zero-valent iron filler added to the anaerobic reaction device is 0.5% to 5% of the volume of the reaction zone of the anaerobic reaction device, and the nano zero-valent iron filler operates in the anaerobic reaction device for 30 to 90 days or 30 days or 90 days or 60 days.

[0098] Step 2: Crushing. Specifically, when the composite nano zero-valent iron filler put into the anaerobic reaction device appears purple and / or brown, preferably 80% or more of the composite nano zero-valent iron filler appears purple and / or brown, 10% to 50%, 10%, 50% or 30% of the composite nano zero-valent iron filler is separated from the reaction zone of the anaerobic reaction device for crushing.

[0099] Step 3: Cultivation, transferring the nano zero-valent iron filler crushed in the second step to the cultivation area of ​​the anaerobic reaction device for cultivation, and maintaining the normal operation of the anaerobic reaction device;

[0100] Step 4: Storage: The nanometer zero-valent iron filler in the culture area of ​​the anaerobic reaction device is discharged through the mud discharge pipe of the anaerobic reactor, and the discharged nanometer zero-valent iron filler is collected and stored.

[0101] Example 4

[0102] Combination Figure 4 The present embodiment provides an anaerobic reaction device, which includes a hydrolysis reactor 10 and a methanogenic reactor 20. The hydrolysis reactor 10 and the methanogenic reactor 20 are gas-phase connected through a gas delivery pipe 2 and a gas delivery connecting pipe 7. The first port of the three-phase separator gas delivery pipe 2 is connected to the gas collecting chambers of the three-phase separator A11 and the three-phase separator B21, and the second port extends into the hydrolysis reactor 10. The gas delivery connecting pipe 7 is a three-way pipeline, the first port of which is connected to the top of the hydrolysis reactor 10, the second port is connected to the top of the methanogenic reactor 20, and the third port is connected to the gas delivery valve 1, which is used to control the exhaust rhythm of the anaerobic treatment device of the present embodiment.

[0103] The hydrolysis reactor 10 and the methanogenic reactor 20 are connected in water through the circulation pump 51 and the water circulation pipe 5. The water circulation pipe 5 connects the methanogenic reactor 20, the circulation pump 51 and the hydrolysis reactor 10, and the water circulation pipe 5 is connected to the bottom of the methanogenic reactor 20 and the hydrolysis reactor 10. When the equipment is running, the circulation pump 51 can realize the circulation of water in the anaerobic treatment device.

[0104] The hydrolysis reactor 10 is provided with a water inlet distribution pipe 13, a grid A14 and a grid E15 in order from top to bottom, and a flow pusher 16 is also provided between the grid A14 and the grid E15. Among them, a filler crushing area is formed between the grid A and the grid E15, and the apertures of the grid A and the grid E15 are smaller than the apertures of the nano iron water treatment fillers entering the hydrolysis reactor 10. Sewage enters the hydrolysis reactor 10 through the water inlet distribution pipe 13, and the part of the water inlet distribution pipe 13 entering the hydrolysis reactor 10 is provided with uniformly distributed water outlets, and the direction of the water outlets is vertically downward, and the apertures of the grid 14A and the grid E15 are smaller than the apertures of the nano iron water treatment fillers entering the hydrolysis reactor 10.

[0105] Combination Figure 5, the grille A is a mesh plate with an opening and closing function. Specifically, the grille A includes two semicircular perforations 141, a hinge 142, a pull rope A143, an inner wall roller 144, and a top roller 145. The first end of the hinge 142 is fixed to the inner wall of the hydrolysis reactor 10, and the second end is fixed to the perforated plate 141. The straight edge of the perforated plate 141 is connected to the pull rope 143, and the pull rope 143 is respectively connected to the inner wall roller 144 and the upper roller 145. The upper roller 145 is arranged near the water inlet pipe 13, and the pull rope A143 passing through the top roller 145 extends out of the hydrolysis reactor 10 through the water inlet pipe 13. The methanogenic reactor 20 is provided with a feeding device 30, a grid C23 and a water distribution pipe 24 in sequence from top to bottom. The water distribution pipe 24 is directly connected to the water circulation pipe 51. The bottom of the methanogenic reactor 20 is connected with a sludge discharge pipe 6, and the sludge discharge pipe is provided with a sludge discharge valve 61. The water distribution pipe 24 is provided with upper and lower alternating water outlet holes 241 along the direction of the outlet pipe 242. In this design, the water outlet holes 241 on the upper side of the water distribution pipe 24 continuously flush the nano iron water treatment filler in the methanogenic reactor 20, and continuously flush the lower area of ​​the water distribution pipe 24, which can solve the problem of solidification of the granular sludge layer of the anaerobic reaction device of this embodiment, and facilitate the regular discharge of sludge particles in the anaerobic treatment device through the opening and closing of the sludge discharge valve 61.

[0106] The structure of the feeding device 30 of the anaerobic reaction device in this embodiment is as follows: it includes a feeding port 301, a feeding pipe 302, a float 303, a pull rope 304, a roller 305 and a bracket 306. The feeding port 301 is preferably funnel-shaped and connected to the feeding pipe 302. The pull rope 304 is connected to the float 303. After the pull rope 304 is wrapped around the roller 305, it is led out from the feeding port 301. The roller 305 is set on the bracket 306, and the bracket is fixed in the methanogenic reactor 20.

[0107] When in use, the float 303 can be moved away from the discharge port of the feeding device 30 by pulling the rope 304. At this time, the filler can fall into the methane enhanced reactor 20. After the feeding is completed, the pull rope 304 is loosened, and the float 303 blocks the discharge port of the filler device under the buoyancy of the water. The feeding device 30 using the float 303 can enhance the safety of the anaerobic treatment device of this embodiment. On the one hand, the float 303 ensures the good sealing of the methane production reactor. On the other hand, if a cover is set at the feeding port 301, the cover will be easily broken when it is unscrewed for feeding under the pressure of the generated methane gas, causing harm to the operator. The setting of the float 303 can well avoid this problem. Of course, setting a cover at the feeding port 301 can also play a sealing role of the float, but the design of the float is a more preferred solution.

[0108] One end of the filler delivery pipe 4 is connected to the hydrolysis reactor 10, and the other end is connected to the methane reactor 20, which is used to transport the filler in the methanogenic reactor 20 to the hydrolysis reactor 10. As a preferred solution, the horizontal height of the filler delivery pipe 4 connected to the hydrolysis reactor 10 is lower than the horizontal height of the end connected to the methanogenic reactor 10. The preferred angle between the filler delivery pipe 4 and the horizontal plane is 20 to 30 degrees. When it is necessary to transfer the nano iron water treated filler from the methanogenic reactor to the hydrolysis reactor, open the filling valve 41 and adjust the isolation device so that the isolation device no longer hinders the nano iron water treated filler from entering the filler delivery pipe 4. Since the filler delivery pipe 4 has a certain inclination, after the nano iron water treated filler enters the filler delivery pipe 4, it can quickly slide to the hydrolysis reactor 10 under the action of gravity, avoiding the accumulation of the nano iron water treated filler in the filler delivery pipe 4.

[0109] The anaerobic reaction device grid B22 of this embodiment is placed in the methanogenic reactor 20. Preferably, the grid B22 is relatively parallel to the grid C23. The grid B22 is located on the upper side of the grid C23. A methanogenic reaction zone can be formed between the grid B22 and the grid C23. The methanogenic reaction zone is used to accommodate nano iron water treatment fillers. In this scheme, one end of the sewage return pipe 3 is connected to the hydrolysis reactor 10, and the other end is connected to the methane reactor 20. The height of the end connected to the methane reactor 20 is higher than the height of the grid B22 in the methanogenic reactor 20. Preferably, the sewage return pipe 3 is set horizontally. In this scheme, the end of the feeding device 30 extends into the methanogenic reaction zone, the nano iron water treatment filler is directly placed in the methanogenic reaction zone, and the filler delivery valve 41 is closed. The sewage is circulated counterclockwise in the anaerobic treatment device through the water circulation pipe 5, the circulation pump 51 and the sewage return pipe 3. The nano iron water treatment filler moves with the water circulation. When the filler is washed to the position of the grid B22, it is blocked by the grid B22, so that the filler stays in the methanogenic reactor 20.

[0110] The general process of the anaerobic device for nano iron water treatment filler of the present invention is that sewage enters the hydrolysis reactor 10 through the water inlet distribution pipe 13, and the sewage is circulated in the hydrolysis reactor 10 and the methanogenic reactor 20 through the water circulation pipe 5, the circulation pump 51, and the sewage return pipe 3. The feeding device 30 transports the nano iron water treatment filler to the methanogenic reactor 20. After the filler has been initially working in the methanogenic reactor 20 for a period of time, the nano iron water treatment filler is transported to the hydrolysis reactor 10 through the filler delivery pipe 4. After the filler continues to work in the hydrolysis reactor 10 for a period of time, the power of the flow propeller is increased to crush the filler. The crushed filler enters the methanogenic reactor 20 through the water circulation pipe 5, combines with the sludge in the sewage, becomes sludge particles, and is discharged through the sludge discharge pipe 6. The sewage passing through the anaerobic reaction device of this embodiment can be discharged through the outlet weir 8 and the outlet channel 81 on the methane reactor 10.

[0111] Wastewater treatment, water volume 100m 3 / d, COD concentration is 10000-20000 mg / L, pH value is 6.2-7.0, water temperature is 30-35°C, the project uses the anaerobic reaction device designed in Example 4, and after the device has been stably operated for 1 year, the composite nano zero-valent iron filler prepared according to Example 1 is added, combined with the device use steps provided in Example 4 and the filler use method provided in Example 3, the normal operation of the project anaerobic device is maintained, and the equipment operation status is shown in Table 5.

[0112] Table 5 Operation status of biopharmaceutical wastewater project

[0113]

[0114] It can be seen from Table 5 that the addition of nano zero-valent iron filler not only improves the treatment effect of the anaerobic device, but also increases the methane production of the anaerobic device. At the same time, anaerobic granular sludge can be obtained, which has significant technical and economic benefits.

[0115] This embodiment provides an anaerobic reaction device that is used in conjunction with the composite nano zero-valent iron filler of the embodiment, which can effectively solve the sludge mineralization and biological toxicity problems caused by the long-term addition of nano zero-valent iron in the sewage treatment process, and ensure the long-term operation of the anaerobic reaction device. At the same time, the composite nano zero-valent iron filler in the embodiment, after being broken during the use of the anaerobic reaction device, can promote the rapid proliferation of anaerobic sludge particles and enhance the ability of anaerobic digestion of methanogens. At the same time, the sludge particles formed by the broken filler and sludge can be sold after being discharged from the anaerobic treatment device of this embodiment.

[0116] The present invention and its embodiments are described schematically above, and the description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. Therefore, if a person skilled in the art is inspired by it and designs a structural method and an embodiment similar to the technical solution without creativity without departing from the purpose of the invention, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a composite nano zero-valent iron filler, characterized in that: The method comprises the following steps: S10: preparing nano zero-valent iron turbid solution: adding nano zero-valent iron into the dispersant solution and stirring evenly to form nano zero-valent iron turbid solution; S20: preparing a gel-like substance: adding polyvinyl alcohol, sodium alginate, carboxymethyl cellulose, EDTA, and EPS-microbial agent into water and stirring until a uniform paste is formed to form a gel-like substance; S30: adding a light porous sponge: weighing the nano zero-valent iron turbid liquid and the gel-like substance according to a weight ratio, stirring them evenly to form a nano zero-valent iron turbid liquid gel-like substance, and adding a light porous sponge so that the nano zero-valent iron turbid liquid gel-like substance is adsorbed on the light porous sponge; S40: Cross-linking and hardening: The lightweight porous sponge adsorbing the nano zero-valent iron turbid liquid gel-like substance is added to a saturated boric acid solution containing 2% to 3% calcium chloride, and hardened and cross-linked for 10 to 20 hours to prepare a nano zero-valent iron composite filler; In the steps S10 to S40, nitrogen is continuously introduced for protection; The weight components of the nano zero-valent iron turbid solution in step S10 are: 40-50 parts of nano zero-valent iron and 50-60 parts of dispersant solution; The dispersant solution described in step S10 comprises: water, starch, dextrin, acetylacetone and ascorbic acid, and the weight components of the dispersant solution are: 85-95 parts of water, 3-8 parts of starch, 0.5-1 part of dextrin, 1-5 parts of acetylacetone, and 0.5-1 part of ascorbic acid; The gel-like substance described in step S20 is composed of 10 to 20 parts by weight of polyvinyl alcohol, 5 to 10 parts of sodium alginate, 4 to 8 parts of carboxymethyl cellulose, 6 to 12 parts of EDTA and 50 to 75 parts of EPS-microbial agent.

2. The method for preparing a composite nano zero-valent iron filler according to claim 1, characterized in that: The EPS-microbial agent is composed of extracellular polymers and microbial liquid in a weight ratio of 1:50, and the colony count of the microbial liquid is 1×10 9 ~1×10 10 cfu / mL.

3. The method for preparing a composite nano zero-valent iron filler according to claim 2, characterized in that: The microorganisms in the microbial liquid include one or more of hydrolytic bacteria, fermentative bacteria, acetic acid bacteria, and methanogens, and the microbial liquid includes trace elements such as Zn, Mn, Co, Ni, Mo, and Se.

4. The method for preparing a composite nano zero-valent iron filler according to claim 1, characterized in that: The water temperature in step S20 is 50-60 degrees Celsius, and the water temperature duration is 10-30 minutes.

5. The method for preparing a composite nano zero-valent iron filler according to claim 1, characterized in that: The weight ratio of the nano zero-valent iron turbid liquid to the gel-like substance in step S30 is 1:3; the lightweight porous sponge in step S30 is a cubic or spherical particle, the side length of the cube and the diameter of the sphere are 8~10mm, the pore size of the particle is 20~30PPI, and the density is 0.5~0.7g / cm³.

6. A composite nano zero-valent iron filler, characterized in that: The composite nano zero-valent iron filler is prepared by the preparation method of any one of requirements 1 to 5, comprising nano zero-valent iron, a dispersant solution, a gel-like substance, and a lightweight porous sponge; the dispersant solution comprises water, starch, dextrin, acetylacetone, and ascorbic acid; the gel-like substance comprises polyvinyl alcohol, sodium alginate, carboxymethyl cellulose, EDTA, and EPS-microbial agent.

7. The composite nano zero-valent iron filler according to claim 6, characterized in that: The weight components of the dispersant solution are: 85-95 parts of water, 3-8 parts of starch, 0.5-1 part of dextrin, 1-5 parts of acetylacetone, and 0.5-1 part of ascorbic acid; the weight components of the gel-like substance are: 10-20 parts of polyvinyl alcohol, 5-10 parts of sodium alginate, 4-8 parts of carboxymethyl cellulose, 6-12 parts of EDTA, and 50-75 parts of EPS-microbial agent.

8. The composite nano zero-valent iron filler according to claim 6, characterized in that: The density of the composite nano zero-valent iron filler is 0.98-1.15 g / cm 3 , the shape is a sphere and / or a cube, the side length of the cube and the diameter of the sphere are 8~10mm.

9. The method for using the composite nano zero-valent iron filler according to any one of claims 6 to 8, characterized in that: The steps include: Step 1: Add the composite nano zero-valent iron filler into the anaerobic reaction device and run it for 30 to 90 days; Step 2: crushing: when the nano zero-valent iron filler put into the anaerobic reaction device turns purple or brown, 10% to 50% of the nano zero-valent iron filler is separated and crushed; Step 3: Cultivation, transferring the nano zero-valent iron filler crushed in the second step to the cultivation area of ​​the anaerobic reaction device for cultivation, and maintaining the normal operation of the anaerobic reaction device; Step 4: Storage: The nanometer zero-valent iron filler in the culture area of ​​the anaerobic reaction device is discharged through the mud discharge pipe of the anaerobic reaction device, and the discharged nanometer zero-valent iron filler is collected and stored.

Citation Information

Patent Citations

  • A method for preparing zero-valent nano-iron particles

    CN104308173B

  • Porous nano-zero valent iron and porous nano-zero valent iron composites

    CN105081305B

  • Method for preparing zero-valence nano-iron particles

    CN104308173A

  • Preparation method and application of nanometer zero-valent ion composite material

    CN106745645A